2013
DOI: 10.1089/hum.2012.250
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of Adeno-Associated Virus–Mediated Alpha-Glucosidase Gene Therapy to the Diaphragm for Chronic Respiratory Failure in Pompe Disease: Initial Safety and Ventilatory Outcomes

Abstract: Pompe disease is an inherited neuromuscular disease caused by deficiency of lysosomal acid alpha-glucosidase (GAA) leading to glycogen accumulation in muscle and motoneurons. Cardiopulmonary failure in infancy leads to early mortality, and GAA enzyme replacement therapy (ERT) results in improved survival, reduction of cardiac hypertrophy, and developmental gains. However, many children have progressive ventilatory insufficiency and need additional support. Preclinical work shows that gene transfer restores phr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 52 publications
1
109
0
4
Order By: Relevance
“…1,3,7,18). Several independent groups have concluded that neuropathology has a significant impact on motor function (8,49,54), but no current therapies are aimed at improving the efferent neural regulation of the respiratory muscles (although a gene therapy clinical trial is in progress [55]). In the context of the current results, it must be emphasized that rigorously controlled in vitro and in vivo experiments indicate that CX717 robustly increases respiratory activity when respiratory neuromotor activity is suppressed, but has minimal impact under conditions of "normal" respiratory motor activity (14,20,47).…”
Section: Discussionmentioning
confidence: 99%
“…1,3,7,18). Several independent groups have concluded that neuropathology has a significant impact on motor function (8,49,54), but no current therapies are aimed at improving the efferent neural regulation of the respiratory muscles (although a gene therapy clinical trial is in progress [55]). In the context of the current results, it must be emphasized that rigorously controlled in vitro and in vivo experiments indicate that CX717 robustly increases respiratory activity when respiratory neuromotor activity is suppressed, but has minimal impact under conditions of "normal" respiratory motor activity (14,20,47).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are ongoing and completed clinical trials using rAAV as a therapeutic tool to treat diseases affecting skeletal muscle ( Mendell et al, 2009( Mendell et al, , 2010Bowles et al, 2012). For example, work with rAAV in animal models has led to the development of a gene therapy strategy for Pompe disease, which has resulted in a clinical trial of rAAV-mediated gene-based therapy for this disease (ClinicalTrials.gov Identifier: NCT00976352) Pacak and Byrne, 2011;Smith et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…79 First clinical trials of gene transfer treatment in five ventilator-dependent Pompe patients demonstrated acceptable safety outcomes and longer periods of unassisted breathing. 80,81 Genome editing via CRISPR/Cas9 82 is another revolutionary approach that might tremendously change the therapeutic options for Pompe patients by modulating disease-causing alleles. However, this approach is yet far away from clinical trials.…”
mentioning
confidence: 99%